TRADITIONAL GAME OF WARA GHERI FOR CHILDREN’S CHARACTER BUILDING MEDIA IN ENDE - Robertus Afrianus Nanga Noo; Theodorus Sutomo Dopen Hurint (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Game is one of the traditional media for character building. One of the traditional games in the district of Ende, Flores, NTT is Wara Gheri means 'angin literally scratching'. The community is also often called the